2013
DOI: 10.3947/ic.2013.45.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Antimicrobial Therapy of Pediatric Urinary Tract Infections Caused by Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae

Abstract: BackgroundThe purpose of this study was to compare the outcome of carbapenem versus non-carbapenem antimicrobial therapy for pediatric urinary tract infections (UTIs) caused by extended-spectrum β-lactamase (ESBL) producing Enterobacteriaceae.Materials and MethodsFrom 2006 to 2011, 42 episodes of UTI caused by ESBL-producing Enterobacteriaceae were diagnosed at Seoul National University Children's Hospital. Patients were grouped according to the antimicrobials they received into a carbapenem group and a non-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
3
31
1
8
Order By: Relevance
“…As expected, we observed a high rate of E coli in samples of ESBL-producing bacteria (19), but more importantly, the rate of infection with Klebsiella was higher in the ESBL group than in the non-ESBL group. Travel abroad during the previous six months, by the patient or their family, was not a significant risk factor in our case study, whereas this was identified as a risk factor in other studies (8,20). Travel abroad during the previous six months, by the patient or their family, was not a significant risk factor in our case study, whereas this was identified as a risk factor in other studies (8,20).…”
Section: Discussioncontrasting
confidence: 66%
“…As expected, we observed a high rate of E coli in samples of ESBL-producing bacteria (19), but more importantly, the rate of infection with Klebsiella was higher in the ESBL group than in the non-ESBL group. Travel abroad during the previous six months, by the patient or their family, was not a significant risk factor in our case study, whereas this was identified as a risk factor in other studies (8,20). Travel abroad during the previous six months, by the patient or their family, was not a significant risk factor in our case study, whereas this was identified as a risk factor in other studies (8,20).…”
Section: Discussioncontrasting
confidence: 66%
“…ESBL producing bacteria causing infections in children may have various complications and adverse outcomes [30]. ESBL producers are non susceptible to aminopenicillins and ureidopenicillins as well as extended-spectrum β-lactam agents like second- and third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…Keduanya menghasilkan angka treatment success rate yang sama-sama 100%. 15 Tidak ada pedoman khusus pada terapi pasien ISK oleh bakteri penghasil ESBL. Studi terkait perbandingan penggunaan terapi, terutama pada pasien anak masih sedikit.…”
Section: Hasilunclassified
“…Meskipun nonkarbapenem diberikan untuk strain resisten, konsentrasi yang relatif tinggi dapat menyebabkan keberhasilan pengobatan walaupun bertentangan dengan hasil uji kepekaan antimikroba. 15 Penggunaan antibiotik nonkarbapenem sebelum pasien kemudian beralih terapi karbapenem digolongkan dalam kelompok terapi karbapenem. Hal tersebut tidak bisa disimpulkan bahwa pemakaian karbapenem sesuai hasil uji sensitivitas tidak dipengaruhi antibiotik lain sebelumnya.…”
Section: Hasilunclassified